Exceptional Crimes, Codification, and Human Rights: Reconstructing Lex Specialis in Indonesia’s Penal Reform - Roni Efendi; Aria Zurnetti; Khairani (Alfuad: Jurnal Sosial Keagamaan, 2026)
The enactment of Indonesia’s Law No. 1 of 2023 on the Criminal Code represents a paradigmatic shift toward a fully codified legal system through an open codification model. While this reform seeks to modernize national criminal law and dismantle the colonial legacy of the Wetboek van Strafrecht, it simultaneously generates a fundamental normative tension concerning the legal status of exceptional crimes traditionally governed by special statutes. This tension raises broader concerns regarding the protection of human rights in the governance of extraordinary crimes, particularly in balancing legal certainty, institutional authority, and the need for exceptional enforcement mechanisms. This article aims to examine whether the incorporation of core offenses such as corruption, terrorism, gross human rights violations, narcotics, and money laundering into Chapter 35 of the new Criminal Code transforms their legal character, enforcement regimes, and human rights implications. Using a normative juridical method with statutory and conceptual approaches, this study analyzes the structural consequences of this integration within a broader framework of codification and legal pluralism. The article argues that Chapter 35 does not dilute the exceptional nature of these crimes nor undermine the operation of the lex specialis derogat legi generali principle. Instead, it establishes a layered and hybrid normative framework in which the Criminal Code functions as an internal special regime that systematically interacts with external special laws while preserving institutional authority. This study further proposes a reconceptualization of lex specialis as a multi-dimensional construct encompassing material specificity, differentiated sanctioning regimes, institutional design, and human rights safeguards. By situating Indonesia’s penal reform within broader debates on codification and legal pluralism, this article contributes to comparative discussions on how contemporary legal systems reconcile unified codification with the protection of fundamental rights in addressing exceptional crimes.